2023
DOI: 10.1097/md.0000000000033279
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio can predict overall survival in patients with stage II to III colorectal cancer

Abstract: The neutrophil-to-lymphocyte ratio (NLR) is a prognostic inflammatory marker in colorectal cancer (CRC), however, little is known for its prognostic role in stage II to III CRC patients underwent curative resection. This study was aimed to investigate prognostic role of NLR in stage II to III CRC patients underwent surgery. Medical records of 1378 newly diagnosed CRC patients between June 2006 and March 2020 were reviewed. Data were collected by using electronic medical record software. Survival rate were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…[23] Cho et al found that a preoperative NLR over 3.15 is associated with poorer overall survival in patients with stage II to III CRC. [24] Another systematic review of 10,259 patients from 19 studies showed that NLR >5.0 was associated with poorer long-term survival in CRC patients. [22] Despite the difference in cutoff values, various studies have confirmed the correlation between the NLR and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Cho et al found that a preoperative NLR over 3.15 is associated with poorer overall survival in patients with stage II to III CRC. [24] Another systematic review of 10,259 patients from 19 studies showed that NLR >5.0 was associated with poorer long-term survival in CRC patients. [22] Despite the difference in cutoff values, various studies have confirmed the correlation between the NLR and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized Penalized and Unpenalized Cox models to assess individuals’ survival rates more than 5 years, based on the single hospital database for patients with CRC, which was published in 2023. [ 7 ] To enhance the depth and reliability of our performance evaluation, we developed and evaluated 100 individual ML models, while also focusing on improving interpretability to identify significant variables. We conducted thorough calculations to measure the individual’s survival probability more than 5 years for performance evaluation, and identified solutions to address challenges of the interpretability stemming from the black box nature of ML.…”
Section: Methodsmentioning
confidence: 99%
“…The database was a medical records of 1378 patients with CRC at a single university hospital between June 2006 and March 2020. [ 7 ] The detailed information about the generation of clinical data and covariates including demographics, blood tests, pathological findings, and immunochemical tests were described in our previous study. [ 7 ] This study followed the key questions for determining the appropriate model type in ML in medicine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations